2016
DOI: 10.5751/ace-00873-110205
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing tropical habitats for long-distance migratory songbirds: an assessment of habitat quality at a stopover site in Colombia

Abstract: ABSTRACT. Long-distance migratory birds are declining globally and migration has been identified as the primary source of mortality in this group. Despite this, our lack of knowledge of habitat use and quality at stopovers, i.e., sites where the energy for migration is accumulated, remains a barrier to designing appropriate conservation measures, especially in tropical regions. There is therefore an urgent need to assess stopover habitat quality and concurrently identify efficient and cost-effective methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Indeed, with time-minimiation emerging as the main currency shaping the evolution of migration strategies (Alerstam 2011), migratory birds are expected to seek out sites that maximize their fuel deposition rate and, accordingly, their speed of migration (Buler et al 2007, La Sorte et al 2014a. It follows that one of the fundamental needs of migratory birds is therefore the availability of high quality habitats (those supporting high fuel deposition rates), in specific regions along their migratory route (Weber et al 1999, Bayly et al 2016. These habitats Figure 1.…”
Section: Full Service Hotelmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, with time-minimiation emerging as the main currency shaping the evolution of migration strategies (Alerstam 2011), migratory birds are expected to seek out sites that maximize their fuel deposition rate and, accordingly, their speed of migration (Buler et al 2007, La Sorte et al 2014a. It follows that one of the fundamental needs of migratory birds is therefore the availability of high quality habitats (those supporting high fuel deposition rates), in specific regions along their migratory route (Weber et al 1999, Bayly et al 2016. These habitats Figure 1.…”
Section: Full Service Hotelmentioning
confidence: 99%
“…For example, in northern Colombia, where geolocators have identified a general region used by Veery for autumn stopover (Heckscher et al 2011, Hobson andKardynal 2015), it is possible to travel from snow-capped peaks, through humid montane forest, to xeric scrub in less than 100 km. Only through detailed mark-recapture studies within that region has the high value of foothill and pre-montane forest been demonstrated for Veery and other Nearctic-Neotropical migrants (Bayly et al 2012a(Bayly et al , 2016.…”
Section: Findings From Geolocators and Other Tracking Technologiesmentioning
confidence: 99%
“…Shade coffee plantations have been promoted as a biodiversity‐friendly production system that can harbour communities intermediate between those of sun coffee monocultures and remnants of native forest (Jha et al, ; Perfecto, Rice, Greenberg, & VanderVoort, ; Philpott et al, ), so financial tools and social incentives have arisen to prevent their replacement by homogeneous land uses (Perfecto, Vandermeer, Mas, & Pinto, ; Philpott, Bichier, Rice, & Greenberg, ). However, most assessments of the conservation value of tropical agroforestry systems rely heavily on community‐level measures (Hughes, Daily, & Ehrlich, ; Petit & Petit, ), and while there is recent evidence on differences for migrant birds (Bakermans, Vitz, Rodewald, & Rengifo, ; Bayly, Gómez, Hobson, & Rosenberg, ), information on demography and persistence of resident species is still scarce (Gleffe, Collazo, Groom, & Miranda‐Castro, ; Irizarry, Collazo, Pacifici, Reich, & Battle, ; Komar, ; Sánchez‐Clavijo, Arbeláez‐Alvarado, & Renjifo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the conservation value of shaded coffee may be higher in areas of high deforestation and those lacking protected areas, where plantations may be the only forest-like habitat suitable for migrants (Perfecto et al 1996, Bakermans et al 2009). Neotropical migrants have been forced into this agroecosystem in response to the loss of natural habitat, and the quality of shade coffee plantations relative to the native forests from where they were carved is still to be fully addressed (but see Bakermans et al 2009, Bayly et al 2016. While conservation efforts to maintain shade coffee plantations are critical, efforts to restore or protect remaining forest are also needed.…”
mentioning
confidence: 99%